2011
DOI: 10.1167/iovs.11-8330
|View full text |Cite
|
Sign up to set email alerts
|

Müller Glia, Vision-Guided Ocular Growth, Retinal Stem Cells, and a Little Serendipity

Abstract: Hypothesis-driven science is expected to result in a continuum of studies and findings along a discrete path. By comparison, serendipity can lead to new directions that branch into different paths. Herein, I describe a diverse series of findings that were motivated by hypotheses, but driven by serendipity. I summarize how investigations into vision-guided ocular growth in the chick eye led to the identification of glucagonergic amacrine cells as key regulators of ocular elongation. Studies designed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Some of the endogenous signaling molecules (reviewed by Wallman and Winawer (2004)) that have been determined to be involved in chick vision-guided eye growth and myopia development include dopamine (Lauber, 1991; Stone et al, 1989), gamma-aminobutyric acid (GABA) (Chebib et al, 2009; Christian et al, 2013; Stone et al, 2003), insulin-like growth factor-1 (IGF1) and fibroblast growth factor-2 (FGF2) (Ritchey et al, 2012b), N -methyl-D-aspartic acid (NMDA) (Fischer et al, 1998; Fischer et al, 1997), retinoids (Fischer et al, 1999b), and glucagon (Feldkaemper and Schaeffel, 2002; Fischer et al, 1999c; Fischer, 2005; Fischer et al, 2008), which may be one of the most critical signaling molecules (Fischer, 2011). Colchicine has also been determined to affect eye growth and development of myopia (Fischer et al, 1999b).…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the endogenous signaling molecules (reviewed by Wallman and Winawer (2004)) that have been determined to be involved in chick vision-guided eye growth and myopia development include dopamine (Lauber, 1991; Stone et al, 1989), gamma-aminobutyric acid (GABA) (Chebib et al, 2009; Christian et al, 2013; Stone et al, 2003), insulin-like growth factor-1 (IGF1) and fibroblast growth factor-2 (FGF2) (Ritchey et al, 2012b), N -methyl-D-aspartic acid (NMDA) (Fischer et al, 1998; Fischer et al, 1997), retinoids (Fischer et al, 1999b), and glucagon (Feldkaemper and Schaeffel, 2002; Fischer et al, 1999c; Fischer, 2005; Fischer et al, 2008), which may be one of the most critical signaling molecules (Fischer, 2011). Colchicine has also been determined to affect eye growth and development of myopia (Fischer et al, 1999b).…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
“…Fischer (2011) also focused on using chick retinas to demonstrate the regenerative potential of the retina. In damaged chick retinas, Müller glia, a cell type derived from neuroepithelial stem cells and distinct from the CMZ progenitor cells present in fish, amphibians, and birds, undergo de-differentiation to acquire progenitor phenotype, expressing Pax6, Chx10 (Fischer and Reh, 2001), Six3 (Fischer, 2005), Notch1 (Ghai et al, 2010; Hayes et al, 2007), and other factors found in retinal progenitor cells including Klf4 (Todd and Fischer, 2015) and asc11a (Fischer and Reh, 2001).…”
Section: Gene Therapy and Retinal Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraocular injections of glucagon inhibited the proliferation of CMZ progenitors, whereas a glucagon-receptor antagonist stimulated proliferation . Evidence suggests that glucagon released from the bullwhip and mini-bullwhip cells acts in opposition to insulin (or insulin-like growth factor) to regulate precisely the proliferation of retinal progenitors in the CMZ (Fischer, 2011;Fischer et al, 2005Fischer et al, , 2006.…”
Section: Vision-guided Retinal Growthmentioning
confidence: 99%